Neurological implications of preeclampsia, more than eclampsia only - Lacunza Paredes1, Rommel Omar (2016)
Preeclampsia is a multisystemic disease that affects pregnant women; it is the second cause of maternal death in Peru and morbidity is high. The neurologic dysfunction in preeclampsia includes various symptoms, and eclampsia is the most known. Understanding reversible posterior encephalopathy as the explanation of all neurological manifestations in preeclampsia would evolve to endless therapeutic possibilities and interrogations on long term prognosis. Magnesium sulfate appears as the best therapeutic alternative in blocking pathophysiologic phenomena resulting in eclampsia, if it is considered as a reversible posterior encephalopathy.